Theory of law – the basis of formation of professional competence of lawyers - Калюжний, Ростислав Андрійович (Scientific works of Kyiv Aviation Institute. Series Law Journal "Air and Space Law", 2017)
Legal education must ensure its competitiveness in graduate professional field in terms of permanent changes occurring at present in the world, transforming the structure of society, values ​​and attitudes, increased demands on the professionalism of the lawyer, the police in particular. Key role played by innovation literature, which undoubtedly belongs peer-reviewed textbook "Theory of State and Law", prepared by the same department of the National Academy of Internal Affairs under the editorship of Professor SD Husaryeva and AD Tikhomirov.Reviewed the manual "Theory of State and Law" is a collective scientific and methodical publication of Representatives, Department of Theory of State and Law of the National Academy of Internal Affairs, are followers of law school outstanding domestic lawyer Vladimir Vladimirovich Kopyeychykova and thus continue and develop its scientific and legal developments in theoretical understanding of law, the formation of state-national doctrine and thinking, pluralistic vision of the existing political and legal systems, with BP account the current trends of global legal development, perception Ukraine international and European standards of security and protection of human rights. In the peer-reviewed user presents theoretical positions and approaches of both domestic and foreign scholars on major public-legal concepts and categories, and the authors of the textbook and offer their own vision of the relevant definitions and legal structures that reflect the latest trends of modern jurisprudence. This guide theoretical definitions and concepts presented mainly within the national state and legal traditions, particularly in the context of positivist combination of natural and co-tsiolohichnoho approaches to thinking.